Analisis Perbandingan Manajemen Keuangan Ojek Online Dan Ojek Reguler Studi Kasus Kecamatan Duren Sawit Jakarta Timur - M. Koesmawan; Darwin Erhandy; Dede Dahlan (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
In order to meet the needs of living which consists of primary as well as secondary needs, human can work in either a formal or an informal job. One of the informal jobs that is became the subject of this research was to become an ojek driver. Ojek is a ranting motorcycle. Revenue of ojek drivers, accordingly, should be well managed following the concept of financial management. This research was conducted for the driver of the online motorcycle drivers as well as the regular motorcycle drivers they are called “The Ojek”. Ojek’s location is in Kecamatan (subdistrict) Duren Sawit, East Jakarta with 70 drivers of ojeks. The online ojeks earn an average of Rp 100,000 per day, can save Rp 11,000 to 21,000 per day, while, the regular ojek has an average income per day slightly lower amounted to Rp 78,500, this kind of ojeks generally have other businesses and always record the outflow of theirs money. Both the online and regular ojeks feel a tight competition in getting passengers, but their income can help the family finances and both ojeks want a cooperative especially savings and loans, especially to overcome the urgent financial difficulties. Almost all rivers, do not dare to borrow money. They are afraid of can not refund the money as scheduled.